2022
DOI: 10.3389/fphar.2022.863677
|View full text |Cite
|
Sign up to set email alerts
|

New Insight in HDACs: Potential Therapeutic Targets for the Treatment of Atherosclerosis

Abstract: Atherosclerosis (AS) features include progressive hardening and reduced elasticity of arteries. AS is the leading cause of morbidity and mortality. An increasing amount of evidence showed that epigenetic modifications on genes serve are a main cause of several diseases, including AS. Histone deacetylases (HDACs) promote the deacetylation at lysine residues, thereby condensing the chromatin structures and further inhibiting the transcription of downstream genes. HDACs widely affect various physiological and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 146 publications
(164 reference statements)
0
16
0
Order By: Relevance
“…Emerging research works have demonstrated that astrocyte was the major regulator of neurotransmitter homeostasis, and activated astrocyte was associated with neuroinflammation in the pathological process of NP (Lee et al, 2018). In the present study, both real-time Histone deacetylases (HDACs) are key regulators in epigenetic modifications and restrain gene expression in multiple diseases by medicating the interactions between histones and transcription factors (Luan et al, 2022). Several studies have found that HDAC1, HDAC2, HDAC4, HDAC5, SIRT1, and SIRT2 were involved in NP (Lin et al, 2015;Miao et al, 2020;Penas & Navarro, 2018).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Emerging research works have demonstrated that astrocyte was the major regulator of neurotransmitter homeostasis, and activated astrocyte was associated with neuroinflammation in the pathological process of NP (Lee et al, 2018). In the present study, both real-time Histone deacetylases (HDACs) are key regulators in epigenetic modifications and restrain gene expression in multiple diseases by medicating the interactions between histones and transcription factors (Luan et al, 2022). Several studies have found that HDAC1, HDAC2, HDAC4, HDAC5, SIRT1, and SIRT2 were involved in NP (Lin et al, 2015;Miao et al, 2020;Penas & Navarro, 2018).…”
Section: Discussionmentioning
confidence: 78%
“…Histone deacetylases (HDACs) are key regulators in epigenetic modifications and restrain gene expression in multiple diseases by medicating the interactions between histones and transcription factors (Luan et al, 2022). Several studies have found that HDAC1, HDAC2, HDAC4, HDAC5, SIRT1, and SIRT2 were involved in NP (Lin et al, 2015; Miao et al, 2020; Penas & Navarro, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the involvement of these components in ganglioside synthesis in VSMCs is speculated, it is required to clarify their contribution in the future. Accumulating evidence suggests a critical role for HDACs in regulating vascular cell homeostasis and atherosclerosis ( Chen et al, 2020 ; Luan et al, 2022 ). Sun et al ( Sun et al, 2020 ) reported that HDAC1 is critical for the migration and phenotypic switching of aortic VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetyltransferases loosen the nucleosome by transferring the acetyl group to histones to facilitate gene transcription. Conversely, histone acetyltransferases remove the acetyl group, promoting histone-DNA interactions and increasing nucleosome compaction [ 174 ]. Histone deacetylases are classified into four groups, and their activities depend on either zinc or NAD + .…”
Section: Introductionmentioning
confidence: 99%